Simplified Method to Measure the Peripapillary Choroidal Thickness Using Three-dimensional Optical Coherence Tomography - Oh, Jaeryung; Yoo, Chungkwon; Yun, Cheol Min; Yang, Kyung-Sook; Kim, Seong-Woo; Huh, Kuhl (Korean journal of ophthalmology, 2013)
To evaluate a simplified method to measure peripapillary choroidal thickness using commercially available, three-dimensional optical coherence tomography (3D-OCT). 3D-OCT images of normal eyes were consecutively obtained from the 3D-OCT database of Korea University Medical Center On the peripapillary images for retinal nerve fiber layer (RNFL) analysis, choroidal thickness was measured by adjusting the segmentation line for the retinal pigment epithelium to the chorioscleral junction using the modification tool built into the 3D-OCT image viewer program. Variations of choroidal thickness at 12 sectors of the peripapillary area were evaluated. We were able to measure the peripapillary choroidal thickness in 40 eyes of our 40 participants, who had a mean age of 41.2 years (range, 15 to 84 years). Choroidal thickness measurements had strong inter-observer correlation at each sector (r = 0.901 to 0.991, p < 0.001). The mean choroidal thickness was 191 ± 62 µm. Choroidal thickness was greatest at the temporal quadrant (mean ± SD, 210 ± 78 µm), followed by the superior (202 ± 66 µm), nasal (187 ± 64 µm), and inferior quadrants (152 ± 59 µm). The measurement of choroidal thickness on peripapillary circle scan images for RNFL analysis using the 3D-OCT viewing program was highly reliable and efficient.